Effect of Narrow-Band Ultraviolet B Phototherapy and Methotrexate on MicroRNA (146a) Levels in Blood of Psoriatic Patients - Asmaa M. Ele-Refaei; Fatma M. El-Esawy (Dermatology Research and Practice)
Background. Recently, some miRNAs have been proven to show aberrant expression in psoriasis and play a role in the pathogenesis of the disease. Objective. To find out whether NB-UVB or methotrexate treatment affects whole blood levels of human miRNA (146a) in patients with psoriasis and demonstrate its correlation with disease severity. Methods. Blood samples were obtained from healthy control and from psoriatic patients before and 12 weeks after treatment with NB-UVB, methotrexate. Quantification of human miRNA (146a) by Real Time PCR (RT-PCR). Results. Blood human miRNA (146a) levels were higher in patients with psoriasis than those in healthy controls (P=0.001); it had no significant positive relation with PASI scores in patients (r=0.2, P=0.107). Real Time PCR showed that, after 12 weeks of treatment with NB-UVB phototherapy or treatment with methotrexate, there was significantly decreased level of miR146a (P=0.001; P=0.002, resp.). Conclusion. The expression of miRNA146a is increased in whole blood samples from psoriasis patients, so we can evaluate its possibility to work as a future therapeutic objective in the treatment of psoriasis. With these markers, it is able to screen therapeutics effect or changes to a further aggressive treatment for psoriasis.